Comparison of operational strategies for nitrogen removal in aerobic granule sludge sequential batch reactor (AGS-SBR): A model-based evaluation. Issue 5 (October 2019) - Sun, Feng; Lu, Yiming; Wu, Jun
Graphical abstract: Highlights: DO control strategy for SND in aerobic granular sludge SBR was evaluated. The Feedback DO control could not cope with the dynamic influent feeding condition. Pre-denitrification, high DO aeration and low DO SND serial reaction mode offered better nitrogen performance. Abstract: The nitrogen removal in the aerobic granule sludge sequential batch reactor (AGS-SBR) could be operated as two modes: the simultaneous nitrification and denitrification (SND) mode and the denitrification-nitrification reaction in serials mode. It is not clear which mode deliver better nitrogen removal performance. In this study, the performance of the two operation modes and their control strategies were evaluated in three operation scenarios (A, B and C) based on mathematical model simulation. The control strategy for the SND in AGS-SBR involved the dissolved oxygen (DO) concentration control, in which the DO was manipulated to optimize nitrogen removal (scenario A). The denitrification-nitrification AGS-SBR was achieved by pre-denitrification, high DO nitrification and low DO SND configuration. In the operation scenario B, the duration of high DO nitrification was manipulated to produce optimized nitrogen removal. The duration for pre-denitrification, high DO nitrification and low DO SND were fixed for the operation scenario C, without using control strategies. The results indicated that operation scenario B and C produced better performance than scenario A in terms of nitrogen removal. The average TN removal rate was 84.4%, 95% and 92% for the scenario A, B and C respectively. The DO control strategy used in scenario A could not cope with the dynamic influent feeding condition. The pre-denitrification, high DO nitrification and low DO SND operation scenarios demonstrated satisfactory nitrogen removal even without using control strategies.